Influência do sistema de cobertura no comportamento térmico de edificações multifamiliares na Zona Bioclimática Brasileira 2 - Tabarelli, Giceli (2017)
In search of thermal comfort with lower energy consumption, research has been carried out seeking to reduce the thermal load of buildings. In this context, the roof system is evidenced, as it is mainly responsible for the thermal load increase on the last floor of residential buildings during the summer, causing high temperatures and cracks in its components. As a result, this research evaluated the thermal performance of the most common roof systems of multifamily buildings in the Brazilian Zone 2, through the methods recommended by NBR 15.575. In addition, the influence of the roof on the thermal behavior of the building with natural conditioning and the variation of the annual energy consumption of the last floor with artificial conditioning were evaluated. The thermal performance results revealed that the building roof was approved at the intermediate level by using the simplified method. Regarding the computational simulation method, it was disapproved in the summer and approved at the intermediate level in the winter. With the changes made in the roof variables, we noticed that the solar absorptivity has more influence on temperature changes of the environments than the thermal transmittance. Therefore, we suggest the inclusion of a range of values of solar absorptions in the simplified performance method criteria, combined with the limits of thermal transmittance for the roof in the Brazilian Zone 2. As to the thermal behavior of the building with natural conditioning, improvements in the roof system reduced summer temperatures by up to 6.36°C in the critical environment and by up to 31.01°C in the roof. Among these values, the decrease in solar absorptivity was the most expressive, reducing 6.02°C in the environment and 27.48°C in the roof. Roof compositions with better thermal behavior during the summer were those that had low solar absorptivity and high air renewal levels. These compositions also showed good results in the winter, but with the reduction of ventilation and the presence of thermal insulation in the system. With reference to the annual energy consumption of the artificially conditioned floor, the increase of the thermal transmittance greatly increased the annual consumption of heating and cooling, except in case of cooling when α=0.30. Likewise, the higher the roof absorptivity value, the higher the cooling expenditure and the lower the heating consumption. Comparing the annual energy consumption with a low solar absorptivity value in the roof, we observed that the thermal transmittance had more influence on the heating consumption. On the other hand, with high absorptivity, the total increase of the expenditure is even higher and more significant for the environment cooling